Multiple Traditional Chinese Medicine interventions for idiopathic pulmonary fibrosis: A protocol for systematic review and meta-analysis of overview. Issue 39 (25th September 2020) - Zhang, Hao-Yang; Pang, Li-Jian; Lv, Xiao-Dong; Liu, Chuang; Nan, Ming-Hua
Abstract: Background: The therapeutic strategies of idiopathic pulmonary fibrosis (IPF) tend to be comprehensive. Improving the major symptoms and quality of life (QoL) is as important as postponing the process of fibrosis. However, only pirfenidone and nintedanib conditionally recommended by guidelines and no definite proof indicate that they can significantly ameliorate the main symptoms and QoL of IPF sufferers. At present, multiple types of Traditional Chinese Medicine (TCM) interventions alone or in combination with conventional western medicine managements are widespreadly applied in IPF treatment, which seemingly have a promising clinical effect, especially in ameliorating the main symptoms and improving QoL. Subsequently, the number of relevant studies in systematic reviews(SRs) and meta-analyses of randomized controlled trials(RCTs) increased significantly. Hence, we plan to implement an overview to collect, evaluate, and summarize the results of these SRs. Methods: An all-round literature retrieval will be conducted in 9 electronic databases, including PubMed, EMBASE, CINAHL, Cochrane Library, Epistemonikos, CNKI, CBM, Wanfang, and VIP. We will focus on the systematic review and meta-analysis of RCTs for multiple TCM interventions alone or in combination with routine western medicine measures in IPF treatment. The main outcomes we follow with interest include the improvement of major symptoms (cough, dyspnea) and QoL. Secondary outcomes will consist of minor symptoms improvement, clinical total effective rate, lung function, blood gas analysis, 6-minute walk text, adverse events, acute exacerbation, all-cause mortality, and IPF-related mortality. Two reviewers will independently select the SRs satisfactory with the enrolling criteria, extract key characteristics, and datas on predefined form, evaluate methodological quality by AMSTAR-2, ROBIS and PRISMA tools, and the quality of evidences adopting GRADE method. In case of any divergence will be reached an agreement by discussion or adjudicated by a third senior reviewer. We will perform a narrative synthesis of the proofs from SRs included. Results: The findings of this overvew will be presented at relevant conferences and submitted for peer-review publication. Conclusions: We expect to obtain comprehensive and reliable evidence of IPF treated by diversified TCM interventions from the potential standard SRs, which may provide suggestions for future RCTs and SRs. Registration number: INPLASY 202080110